ONGOING SUPERVISED STAFF TRAINING MODEL : A THEORETICAL PLATFORM FOR HIGH-ORDER THINKING SKILLS COACHING IN A MULTI-DISIPLINARY ENVIRONMENT - Nassie, Irit M. (European Scientific Journal, ESJ, 2015)
This is an ongoing process of staff-training combined with self-study conducted simultaneously by the team of Inspire-Academy, a privately initiated venture aimed at embedding high order thinking-skills in the functional routine of children and their significant adults. The team comprises of the academic principal and three staff trainers. The venture is an advanced and improved offspring of two initiatives undertaken and researched during institutionalized teacher training anchored in an innovative paradigm – MOST84 (Nassie, Shani & Bar-on 2008) and Multiple MOST85- (Nassie & Shani, 2009). Having witnessed the impact MOST and had on training and teaching of language arts, Multiple MOST has been introduced consecutively into three training disciplines: Literacy, Mathematics and Art. Disciplines were chosen as a platform for meditative procedures using the language of thinking, due to their close link to language and to thinking. Five years of supervised practice in elementary schools called for widening and adjustments to fit early childhood coaching by professionals of Inspire- Academy to youngsters’ significant adults through By-Proxy-Mediation. 86 The benefits of the extended model as a platform for simultaneously training young children and their care takers is investigated. ECMMI was used to train two groups of which the writer was the moderator: Group One consisted of instructors of Inspire-Academy as part of their injob training. Group Two – comprised of non-professional-adults – parents, grand parents and care givers seeking to maximize their meditative-coaching skills for the benefit of the young children they cater to. Insights gained through practitioner-reflection resulted in changes in model which is now under intensive investigation.